Fabrication of high thermal conductivity silicon nitride ceramics by pressureless sintering with MgO and Y2O3 as sintering additives. Issue 17 (1st December 2020) - Lu, Tao; Wang, Tun; Jia, Yingfei; Ding, Maomao; Shi, Ying; Xie, Jianjun; Lei, Fang; Zhang, Lei; Fan, Lingcong
Abstract: The fabrication of silicon nitride (Si3 N4 ) ceramics with a high thermal conductivity was investigated by pressureless sintering at 1800 °C for 4 h in a nitrogen atmosphere with MgO and Y2 O3 as sintering additives. The phase compositions, relative densities, microstructures, and thermal conductivities of the obtained Si3 N4 ceramics were investigated systemically. It was found that at the optimal MgO/Y2 O3 ratio of 3/6, the relative density and thermal conductivity of the obtained Si3 N4 ceramic doped with 9 wt% sintering aids reached 98.2% and 71.51 W/(m·K), respectively. EDS element mapping showed the distributions of yttrium, magnesium and oxygen elements. The Si3 N4 ceramics containing rod-like grains and grain boundaries were fabricated by focused ion beam technique. TEM observations revealed that magnesium existed as an amorphous phase and that yttrium produced a new secondary phase.